Achieving high aspect ratio wrinkles by modifying material network stress. Issue 22 (30th May 2017) - Chen, Yu-Cheng; Wang, Yan; McCarthy, Thomas J.; Crosby, Alfred J.
Abstract : Wrinkle aspect ratio is significantly enhanced by modifying the stress energy in the substrate. Abstract : Wrinkle aspect ratio, or the amplitude divided by the wavelength, is hindered by strain localization transitions when an increasing global compressive stress is applied to synthetic material systems. However, many examples from living organisms show extremely high aspect ratios, such as gut villi and flower petals. We use three experimental approaches to demonstrate that these high aspect ratio structures can be achieved by modifying the network stress in the wrinkle substrate. We modify the wrinkle stress and effectively delay the strain localization transition, such as folding, to larger aspect ratios by using a zero-stress initial wavy substrate, creating a secondary network with post-curing, or using chemical stress relaxation materials. A wrinkle aspect ratio as high as 0.85, almost three times higher than common values of synthetic wrinkles, is achieved, and a quantitative framework is presented to provide understanding the different strategies and predictions for future investigations.